2022
DOI: 10.1002/ps.6909
|View full text |Cite|
|
Sign up to set email alerts
|

Risk assessment and resistance inheritance of triflumezopyrim resistance in Laodelphax striatellus

Abstract: BACKGROUND: Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae) is one of the most important insect pests of rice, and it has been able to develop strong resistance to many insecticides. Triflumezopyrim, a new type of mesoionic insecticide developed by Corteva Agriscience, showed high biological activity in controlling piercing-sucking insect pests such as planthopper and leafhopper.RESULTS: In this study, we continuously selected a susceptible laboratory stain (Unsel) of L. striatellus for 16 generations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…But the resistance was rapidly increased to 26.29-fold after the F 8 generation, reaching the middle resistance level. However, previous study showed SPBH could increase 45.1-fold to TFM only after 16 generations selection ( Zhang et al, 2022 ). This different result may be due to the differences of selection method.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…But the resistance was rapidly increased to 26.29-fold after the F 8 generation, reaching the middle resistance level. However, previous study showed SPBH could increase 45.1-fold to TFM only after 16 generations selection ( Zhang et al, 2022 ). This different result may be due to the differences of selection method.…”
Section: Discussionmentioning
confidence: 88%
“…Frontiers in Physiology frontiersin.org to TFM only after 16 generations selection (Zhang et al, 2022). This different result may be due to the differences of selection method.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations